The Ability of Third Semester Students in Multiple Choice Questions to Assess Literal, Evaluative and Critical Understanding - Susiani, Susiani; Fitri Rizki (Yayasan Darus Soleh Parung, 2026)
This study aims to examine the ability of third-semester students in answering multiple-choice questions designed to assess literal, evaluative, and critical levels of reading comprehension. A quantitative descriptive method was employed using a 30-item multiple-choice test. The participants consisted of 35 third-semester students from an English Course at STIKOM Tunas Bangsa. The results show that the students’ literal comprehension is categorized as “good” (mean = 78), evaluative comprehension as “fair” (mean = 65), and critical comprehension as “poor” (mean = 58). These findings indicate that students still need to develop higher-order reading strategies, especially in the area of critical analysis.